Hukum Jual Beli Hewan Perspektif Undang-Undang Perlindungan Hewan No. 5 Tahun 1990 dan Fiqih Empat Mazhab - Immawan Muhajir Kadim (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
Animal trade activity is the most famous trade activity among society loving animal recently. This animal trade activity has a special customer so it can facilitate the trader to meet the buyer. This is reasonable to be discussed in the animal protective law and fikih four mazhab, Because animal protective law and fikih four madzhab have the classification of animals allowed to be traded and forbidden else. This research comes in the kind of normative research. This research is called the library research. This research comes in normative research that observe on the law basis. The approach used is juridical normative analysis approach. The kind of the approach used on this research is conceptual approach. On this research, analysis datum method used on is qualitative datum analysis. The result of this research shows that we as Islamic faithful followers have to submit and obey with the law made by the government unless it rebels our faith as Muslim. It is on the same matter, when it comes in animal trade, Muslim must obey with the protective animal law made by the government to leave the strange animal on trade business, the animal which it’s population has decreased for year by year and the animal threaten lost a all.